PAVO CRISTATUS FEATHER POWDER AS AN ECO-FRIENDLY AND LOW COST MATERIAL FOR MITIGATION OF Pb(II) IONS FROM WATER - Saini, Suman; Chawla, Jyoti; Kumar, Rajeev; Kaur, Inderpreet (Malaysian Journal of Science, 2021)
Mitigation of Pb(II) ions from water using economic method is an important research area to combat the pollution due to lead ions Pb(II) in water as it have severe toxic effects in human beings. In present work, Pristine Pavo Cristatus feather powder (PCFP) has been employed for removal of Pb(II) ions and the process of adsorption was optimized through four level Box Behnken design (BBD) of response surface methodology (RSM) over a broad range of pH (3.0–9.0), initial lead ion concentration (20–100 mg/L), contact time (20–180 min) and temperature (297 K to 333 K). Different isotherms were applied to confirm the type of adsorption. Langmuir maximum removal efficiency was 121.95 mg/g for lead ions adsorption onto PCPF at optimal values of pH 6; adsorbent dose 20 mg/L; temperature 303 K and contact time 120 minutes obtained from batch studies. Pseudo-second-order reaction model showed good applicability for kinetic studies. Thermodynamic parameters were also evaluated to check feasibility and nature of adsorption. The optimal parameters obtained for maximum Pb(II) ions adsorption were at pH = 6.31, initial Pb(II) ion = 43.79 mg/L, contact time = 119.51 minutes and temperature = 59.67 oC. The experimental and predicted values were found to be in good agreement with each other.